Concentrations, composition profiles, and in vitro–in silico-based mixture risk assessment of bisphenol A and its analogs in plant-based foods - Chun-Hui Chiu; Shih-Han Sun; Yun-Jia Yao; Yi Chuang; Yu-Tsung Lee; Yi-Jun Lin (Environment International)
The substitution of bisphenol A (BPA) with structurally similar analogs has raised concerns due to their comparable estrogenic activities. Considering the high consumption of plant-based foods, assessing the risks posed by bisphenols (BPs) in such dietary sources is essential. However, limited exposure and animal toxicological data on BP analogs hinder comprehensive risk assessments. This study investigated 16 BPs in 23 plant-based foods from Taiwan and estimated their dietary exposure across age groups. High-throughput toxicokinetic modeling was used to convert in vitro ToxCast estrogen receptor (ER) bioactive concentrations into human-equivalent points of departure (PODs), which were compared to PODs derived from animal studies and applied to assess mixture risks through the margin of exposure based on the common ER pathway. In total, 7 BPs were detected, and most samples (85.9 %) contained detectable concentrations. Total concentrations of the 7 BPs (∑7BP) ranged from 0.06 ± 0.11 ng/g to 26.60 ± 72.18 ng/g, with BPA being the most predominant (63 % of the mean ∑7BP concentrations), followed by bisphenol S (19 %) and 4,4-bisphenol F (13 %). In vitro–in silico-derived PODs were comparable to or even more protective than in vivo animal-derived PODs. For most population groups, combined exposure to multiple BPs from plant-based foods is generally not a risk concern for ER pathway perturbation, although potential concerns in worst-case scenarios cannot be excluded. This study advances the understanding of the dietary risks associated with BP mixtures and illustrates the potential of in vitro–in silico approaches for assessing human health risks from environmental contaminants.